5‐Substituted Derivatives of the Tricyclic (+)‐Sparteine Surrogate in the Enantioselective Lithiation/Stannylation of an O‐Alkyl Carbamate. Issue 33 (2nd October 2013) - Breuning, Matthias; Hein, David
Abstract: 5‐Mono‐ and 5, 5‐disubstituted tricyclic bispidines, derivatives of the known (+)‐sparteine surrogate, have been synthesized in four‐to‐six steps from the natural alkaloid (–)‐cytisine and evaluated as chiral ligands in the enantioselective lithiation/stannylation of an O ‐alkyl carbamate. Structure–selectivity studies revealed that a small 5‐ endo substituent is tolerated, whereas larger 5‐ endo substituents and even small 5‐ exo substituents lead to significantly reduced levels of chirality transfer. Abstract : Novel tricyclic bispidines have been synthesized from the readily available alkaloid (–)‐cytisine and evaluated in the enantioselective lithiation/stannylation of an O ‐alkyl carbamate. Structure–selectivity studies revealed that an increased steric demand at the 5‐ endo position is not favorable.